Board Performance Evaluation - Osborne, Simon (World Bank, Washington, DC, 2012)
This guidance is produced to assist companies in understanding, and consequently managing, some of the major issues involved when considering how to carry out board performance evaluation. Different issues will apply to different companies, thus this guidance should not be considered as exhaustive. Hopefully it will trigger the thought processes so that boards may consider for themselves the issues that are appropriate to their own and their company's circumstances. In leading up to these decisions it can be useful to take a step back and try to identify the requirements of a board and the elements which need to be in place in order to achieve the optimum performance.